Misplacement of DJ stent into inferior vena cava in a patient with retroperitoneal fibrosis, a case report - Amir Reza Abedi; Majid Dargahi; Seyed Jalil Hosseini (Urology Case Reports, 2021)
Intravascular migration of DJ stent is a rare complication that needs immediate attention to prevent severe complication. We reported a rare case of intravascular migration of DJ stent in a patient with retroperitoneal fibrosis. The DJ stent was removed by cystoscopy with no complication.